Maternal blood pressure during gestation: the effects of low and high salt intake during pregnancy in normotensive sprague dawley rats - Mohd Noor, Noriah (2015)
Background: Current evidence indicates mixed findings with regard to the effects of low and high maternal dietary salt intake during pregnancy on the maternal blood pressure. Objective: This study investigates the effects of low and high maternal dietary salt intake on the systolic blood pressure (SBP) at third week of gestation as compared to pre-pregnancy SBP. Methodology: 30 female Sprague Dawley normotensive rats were randomly assigned into three groups based on maternal dietary salt concentration; low salt (0.145% NaCl, n=10), normal salt (1.0% NaCl, n =10) and high salt (3.0% NaCl, n=10). Food intake and maternal body weight were recorded. SBP (mmHg) and heart rate (HR) were measured during pre-pregnancy and at third week of pregnancy by using non-invasive tail cuff blood pressure monitoring device. Results: There were comparable pre-pregnancy body weight, mean daily food intake, HR and SBP (116.5± 1.54 vs. 118.07 ± 1.22 vs. 115.83 ± 1.76) among LSD, NSD and HSD dams respectively. There were no significant differences in maternal mean daily food intake throughout the pregnancy, body weight at third week of gestation, HR and SBP (113.67± 2.74 vs. 111.37 ± 1.84 vs. 113.93 ± 2.11) at third week of gestation among LSD, NSD and HSD dams respectively. Statistically significant difference in term of SBP between pre-pregnancy and third week of gestation was only seen in the NSD dams (118.07 ±1.22 vs. 111.37 ±1.84) (P<0.05). HR was comparable among the three dams. Conclusion: The SBP decreases in all maternal groups at third week of gestation. However, within group analysis revealed that only NSD dams has significantly lower SBP at third week of gestation as compared to pre- pregnancy SBP. The decrement of SBP is more pronounced in the NSD dams depicting the possibilities of aberration in the expected cardiovascular physiological changes in LSD and HSD dams.